Financial Intermediation and the Theory of Agency - Draper, Dennis W.; Hoag, James W. (Journal of Financial and Quantitative Analysis, 1978)
Dennis W. Draper, James W. Hoag, Financial Intermediation and the Theory of Agency, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 4, Proceedings of Thirteenth Annual Conference of the Western Finance Association, June 20-26, 1978 (Nov., 1978), pp. 595-611